(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ruthenium-doped Zinc Oxide (ZnO) and Nickel Oxide (NiO) have garnered significant attention for their photocatalytic, and antibiofilm properties, presenting promising avenues for environmental and biomedical applications. This study presents a comparative analysis of the photocatalytic and antibiofilm activities of pure and ruthenium-doped ZnO and NiO. Synthesis methods, structural characterization, and performance evaluation were conducted to assess their effectiveness in photocatalytic degradation and antibiofilm efficacy. The results reveal distinct differences in the photocatalytic and antibiofilm behaviors of pure and ruthenium-doped ZnO and NiO, indicating the influence of dopant type and concentration on their performance. Insights from this comparative analysis provide valuable guidance for the rational design and optimization of metal-doped metal oxide-based photocatalysts and antibiofilm agents for diverse practical applications.